Sex-Specific Relationships between HDL-Cholesterol Levels and 10-Year Mortality in Individuals with Atherosclerotic Cardiovascular Disease: A Nationwide Cohort Study of South Koreans - Hyun Suk Yang; Ho Jin Jeong; Hyeongsu Kim; Seungho Lee; Mina Hur (Metabolites, 2023)
Large epidemiological studies show U-shaped relationships between high-density lipoprotein cholesterol (HDL-C) levels and all-cause mortality in individuals without atherosclerotic cardiovascular diseases (ASCVD). Association in those with ASCVD by sex is unclear. We examined the association between HDL-C levels and 10-year all-cause mortality in subjects (≥40 years of age) with ASCVD using the 2010 National Health Insurance Service and the National Death Registry of Korea. We categorized HDL-C levels into three groups (low: <40 mg/dL for males, <50 mg/dL for females; high: 40–90 mg/dL for males, 50–90 mg/dL for females; extremely high: >90 mg/dL) and 10 mg/dL intervals. We conducted a sex-stratified and adjusted Cox proportional hazards analysis. Out of 1,711,548 individuals (54% female, mean age 61.4 years), 10-year mortality was observed in 218,252 (12.8%). Males had a higher mortality rate than females (16.2% vs. 9.8%; p < 0.001). When adjusting for age, body mass index, LDL-cholesterol, triglycerides, hypertension, diabetes, smoking, and alcohol consumption, the low and extremely high HDL-C groups had significantly higher hazard ratios for 10-year mortality compared to the high HDL-C group in males [1.183 (1.166–1.199), 1.359 (1.288–1.434)] and in females [1.153 (1.138–1.169), 1.095 (1.029–1.167)]. The frequency distribution bars for the 10-year mortality rate showed sex-specific nadirs of 50–59 mg/dL in males and 70–79 mg/dL in females. In this ASCVD cohort, the extremely high HDL-C (>90 mg/dL) group had 35.9% and 9.5% higher 10-year mortality risks than the high HDL-C group for males and females, respectively. There was a slightly U-shaped relationship between baseline HDL-C levels and a 10-year mortality rate, with earlier inflection in males than in females.